Dynamic Stereochemistry of Monobridged Tetraarylethene Naphthologues. Variations of Bistricyclic Aromatic Enes. Issue 12 (20th October 2015) - Assadi, Naela; Pogodin, Sergey; Agranat, Israel
Abstract: Dynamic 1 H NMR experiments on monobridged tetraarylethenes (bistricyclic aromatic enes devoid of one bridge, BAE‐1s) revealed the conformational processes in13 –15 (BAE‐1 s, X=S, Se, and Te) and in their respective thiiranes. The experimental energy barriers Δ G ≠ c were found to be 59.0, 72.2, and 67.9 kJ mol −1 for13, 14, and15, and 63.4, 64.4, and 61.3 kJ mol −1 for26, 27, and28, respectively. In contrast to the bis(α‐naphthyl) derivatives13 –15, no dynamic processes were detected for the bis(β‐naphthyl) derivatives16 –20 . These results are in agreement with the mechanisms of enantiomerization of13 –15 derived from DFT calculations. The folded‐twisted global minima conformers of13 –15 undergo enantiomerization via inversion of the central ring, accompanied by rotation of the α‐naphthyl substituents. The B3LYP/SDD free energy barriers, Δ G 298, for the enantiomerizations of BAE‐1s13 –15 are 57.4, 66.6, and 80.2 kJ mol −1, respectively. The minima and transition‐state conformations are chiral and the enantiomerization may proceed via chiral pathways. Abstract : Ene and out : The dynamic processes in monobridged tetraarylethenes correspond to their enantiomerizations via inversion of the central ring (containing a chalcogen atom X) of their tricyclic moiety. The experimental energy barriers measured by dynamic NMR experiments are Δ G ≠ c = 59.0, 72.2, and 67.9 kJ mol −1 for bis(α‐naphthyl) derivatives13 (X=S), 14 (X=Se), and15 (X=Te). The respective DFT calculated barriers are ΔΔ G 298 =57.4, 66.6, and 80.2.